Establishment of Water Quality Index based on statistical analysis: Application to Huong River, Thua Thien Hue province - Hùng, Nguyễn Việt; Nguyễn, Thị Quyên; Nguyễn, Hải Phong; Hop, Nguyen Van; Nguyễn, Hữu Trung; Lê, Quang Ánh; Đặng, Phước Bình (Hue University Journal of Science: Natural Science, 2021)
Huong River’s water quality was preliminarily assessed by comparing the parameters monitored with the Vietnam Technical Regulation on Surface Water Quality. The river water quality was then assessed based on Water Quality Index (WQI). Principal Component Analysis (PCA) was applied to the river water quality data during 2017–2020 to determine the weighting (wi) of the ith water quality parameter for WQI calculation. The WQI was calculated both from wi and subindex (qi). The parameters selected (n = 11) for WQI calculation consisted of pH, EC (electric conductivity), DO, TSS, BOD5, COD, N-NH4+, N-NO3–, P-PO43–, Fe (total dissolved iron), and TC (total coliform). The parameters were monitored at 8–10 sites in 4–5 sessions (February, May, August, and November). The results show that 95% of WQI at 90–100 corresponds to water quality level ‘good’ and ‘excellent’; only 5% of WQI values at 49–77 (mainly in November 2020) corresponds to the level from ‘bad’ to ‘good’. In the flood-rainy season, the increase in concentrations of TSS and Fe and the decrease in DO concentration lead to a reduction in WQI. The river water quality was not significantly differed by space/monitoring sites (p > 0,05) with median WQIs of 97–100 but varied over time: the years 2017 and 2019 had median WQIs (99), higher than that in the years 2018 and 2020 (97) with p < 0,01.